The determinants and impact of outsourcing on airlines' performance - Tayeb, Mamdouh Taher (2012)
This thesis is concerned with the impact of outsourcing within the airline industry. There are conflicting viewpoints on the impact of outsourcing and a scarcity of empirical studies examining its influence on the airlines' performance. In order to fill in this gap, the research process was divided into three stages: (1) Literature review and an exploratory case study; (2) Analysis of secondary data; and (3) Qualitative analysis of 14 interviews, representing 12 different airlines. Through the study, the determinants of outsourcing and current outsourcing practices within the airline industry were identified. Cost reduction and enhancing the focus on core activities were identified as the main motives for outsourcing. Local authorities' legislation is regarded as the main influential external factor while demand level for a given function, criticality of the activity being considered for outsourcing, and current capability status of performing the activity are identified as the main influential internal factors. Most outsourcing arrangements are being made outside the airlines' home bases. The implications of outsourcing in the performance objectives (cost, delivery, quality, and flexibility) as well as in the airlines' overall operational performance were also evaluated. The evaluation of the airlines' performance was based on the 'passenger load factor' and 'daily aircraft utilisation'. The former captures the airlines' operational efficiency. The latter refers to maximising aircraft utilisation, one of the main tasks for the airline management. Although a positive impact on the cost objective was found, it is strongly correlated with the demand level for the outsourced function. The delivery objective is negatively influenced by outsourcing. The outsourcing influence on quality varies, depending on the nature of the outsourced function. The flexibility objective is positively influenced by outsourcing. The study revealed that there is no direct impact of outsourcing on the airlines' overall operational performance. Two main contributions were provided through the research: theoretical and practical. On a theoretical level, a more in-depth understanding of the outsourcing determinants, current practices, and performance implications in the airline industry was provided. The study also represents practical guidance for new entrants in devising their supply chains and assisting managers in terms of supply chain restructuring by predicting the determinants and impact of outsourcing on the airlines' operational performance.